RESISTANCE TO COMPACTION/BALING OF RECYCLABLE CARDBOARD WASTE USING STATIONARY HORIZONTAL PRESSES - PAULA TUDOR; BIANCA-STEFANIA ZABAVA; GHEORGHE VOICU; MIRCEA-BUCUR LAZEA; GABRIEL-ALEXANDRU CONSTANTIN (Journal of Engineering Studies and Research, 2024)
The paper presents the resistances to the formation of a bale of recyclable cardboard, in the ten stages of its formation, up to binding, as well as on each stage separately, for the pressing phase and for the expansion phase, until the start of a new cycle, including the mass variation of the bale in formation. It also presents the energy accumulated in the bale for each phase of its formation, and the total energy required for its formation. The presented data can be used both by the builders of balers for pressing and baling recyclable waste, and by their users to make the best settings.